Telling the story in the data : narrative writing for doctoral students and qualitative researchers - Heller, Caroline E.; Hansen, David T., 1952- (New York : Teachers College Press, 2023)
Traditional dissertations aiming to illuminate the landscapes of education are often too poorly written to have far-reaching readership. This book examines the inner workings of a doctoral course focused on teaching qualitative researchers strong narrative writing. By the time doctoral students finish their dissertation research, bolstered by theoretical grounding and time in the field, they are in a unique position to offer insights about education that should be heard in the public arena, not just during dissertation defenses. For this to happen, doctoral students need to know how to achieve their writerly goals. This book focuses on helping doctoral students and all qualitative researchers do just that. It is also an excellent resource for professors teaching narrative writing. Readers will learn how to use narrative writing to "tell the story in the data" so their research will be read and potentially infuse policy decisions with the complexity such considerations deserve.
Includes bibliographical references and index.
Keywords: Dissertations, Academic -- Authorship; Education -- Research -- Study and teaching (Graduate); Qualitative research; Narration (Rhetoric) -- Study and teaching (Graduate)